Dark Chocolate Intake Positively Modulates Redox Status and Markers of Muscular Damage in Elite Football Athletes: A Randomized Controlled Study. (21st November 2018) - Cavarretta, Elena; Peruzzi, Mariangela; Del Vescovo, Riccardo; Di Pilla, Fabio; Gobbi, Giuliana; Serdoz, Andrea; Ferrara, Roberto; Schirone, Leonardo; Sciarretta, Sebastiano; Nocella, Cristina; De Falco, Elena; Schiavon, Sonia; et al.
Abstract : Intensive physical exercise may cause increase oxidative stress and muscular injury in elite football athletes. The aim of this study was to exploit the effect of cocoa polyphenols on oxidative stress and muscular injuries induced by intensive physical exercise in elite football players. Oxidant/antioxidant status and markers of muscle damage were evaluated in 24 elite football players and 15 controls. Furthermore, the 24 elite football players were randomly assigned to either a dark chocolate (>85% cocoa) intake (n = 12 ) or a control group (n = 12 ) for 30 days in a randomized controlled trial. Oxidative stress, antioxidant status, and muscle damage were assessed at baseline and after 30 days of chocolate intake. Compared to controls, elite football players showed lower antioxidant power and higher oxidative stress paralleled by an increase in muscle damage markers. After 30 days of dark chocolate intake, an increased antioxidant power was found in elite athletes assuming dark chocolate. Moreover, a significant reduction in muscle damage markers (CK and LDH, p < 0.001 ) was observed. In the control group, no changes were observed with the exception of an increase of sNox2-dp, H2 O2, and myoglobin. A simple linear regression analysis showed that sNox2-dp was associated with a significant increase in muscle damage biomarker release (p = 0.001 ). An in vitro study also confirmed that polyphenol extracts significantly decreased oxidative stress in murine myoblast cell line C2C12-derived. These results indicate that polyphenol-rich nutrient supplementation by means of dark chocolate positively modulates redox status and reduced exercise-induced muscular injury biomarkers in elite football athletes. This trial is registered with NCT03288623 .